LHPP inhibits cell growth and migration and triggers autophagy in papillary thyroid cancer by regulating the AKT/AMPK/mTOR signaling pathway. (30th March 2020) - Sun, Wenyu; Qian, Kai; Guo, Kai; Chen, Lili; Xiang, Jun; Li, Duanshu; Wu, Yi; Ji, Qinghai; Sun, Tuanqi; Wang, Zhuoying
Abstract: In recent decades, the incidence rate of papillary thyroid carcinoma (PTC) has been rapidly increasing. However, the molecular mechanism of the physiological and pathological processes of PTC is still largely unknown. Phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) is a tumor suppressor and exerts anti-tumor effect in several human cancers, while the role and underlying mechanism of LHPP in PTC remain vague. In this study, we firstly evaluated the roles of LHPP in PTC and explored its underlying mechanism. Using clinical tissue samples, we detected the level of LHPP in PTC tissues and in matched adjacent normal tissues. Lower level of LHPP was found in PTC tissues than in matched adjacent normal tissues. Similar LHPP expression pattern was found in PTC cell lines when compared with that in normal human thyroid follicular epithelial cells. Then, we over-expressed LHPP in three PTC cell lines and results showed that ectopic LHPP expression consistently reduced cell viability, proliferation, and migration and triggered cell autophagy. Furthermore, over-expression of LHPP inhibited the activation of the AKT/mTOR pathway and promoted the AMPK signaling pathway. In addition, the activation of AKT/mTOR and inhibition of AMPK signaling pathways restored the role of ectopic LHPP expression in PTC cell lines, indicating that LHPP exerts its anti-tumor activity through regulating the AKT/AMPK/mTOR pathway. Ultimately, we illustrated that ectopic LHPP expression inhibited PTC tumor growth in vivo . In conclusion, we revealed that LHPP has an anti-tumor effect in PTC and indicated that LHPP might serve as an effective diagnostic and therapeutic target for PTC.